2005
DOI: 10.1111/j.1600-6143.2005.01055.x
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Late Conversion from CNI‐Based to Sirolimus‐Based Immunosuppression Following Renal Transplantation

Abstract: Maintenance immunosuppression with calcineurin inhibitors (CNIs) following renal transplantation is associated with nephrotoxicity and accelerated graft loss. We aimed to assess whether conversion to sirolimusbased immunosuppression would affect the progression of renal impairment.In this single center, randomized controlled trial, 40 renal transplant recipients between 6 months and 8 years post-transplant were randomly assigned to remain on their CNI (cyclosporin or tacrolimus) or to switch to sirolimus. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
91
1
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 123 publications
(108 citation statements)
references
References 36 publications
(39 reference statements)
9
91
1
7
Order By: Relevance
“…Watson and colleagues examined renal outcomes in patients who were 6 months to 8 years posttransplant with "suboptimal graft function" and found that abrupt CNI discontinuation and SRL conversion resulted in signifi cantly higher GFRs at 3 and 13 months post-conversion. 33 Of note, there was a positive correlation between baseline renal function and change in GFR at 12 months (R 2 = 0.22; p = 0.05), suggesting that the greatest improvement in GFR occurred in SRL-converted patients with better baseline function. Another group utilized post-transplant biopsies and ␣-smooth muscle actin expression to determine the impact of SRL conversion on CAN progression.…”
Section: Mtor-i Conversion After Renal Transplantationmentioning
confidence: 98%
See 1 more Smart Citation
“…Watson and colleagues examined renal outcomes in patients who were 6 months to 8 years posttransplant with "suboptimal graft function" and found that abrupt CNI discontinuation and SRL conversion resulted in signifi cantly higher GFRs at 3 and 13 months post-conversion. 33 Of note, there was a positive correlation between baseline renal function and change in GFR at 12 months (R 2 = 0.22; p = 0.05), suggesting that the greatest improvement in GFR occurred in SRL-converted patients with better baseline function. Another group utilized post-transplant biopsies and ␣-smooth muscle actin expression to determine the impact of SRL conversion on CAN progression.…”
Section: Mtor-i Conversion After Renal Transplantationmentioning
confidence: 98%
“…74 However, infectious complications appear to be more common post conversion. 33,35,[75][76][77] Increased infection risk is more likely to occur early in the post-conversion period and may be associated with slower, gradual tapering of CNI and loading dosages. Immediate cessation or rapid reduction of CNI followed by SRL initiation does not appear to result in major infection.…”
Section: Practical Considerations When Using Mtor-is: It's About Timementioning
confidence: 99%
“…The availability of SRL allows substitution for CNI therapy with a non nephrotoxic agent and potentially avoids risk of acute rejection. 21 No attempt was made in this study to quantify the burden of CAN prior to switching to SRL. 21 We did not do protocol kidney transplant biopsies in our study.…”
Section: Discussionmentioning
confidence: 99%
“…21 No attempt was made in this study to quantify the burden of CAN prior to switching to SRL. 21 We did not do protocol kidney transplant biopsies in our study. Such biopsies could help in documenting the progression of CAN in the low-CAN and high-CAN score groups during the period of follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation